1988
DOI: 10.1002/bjs.1800750605
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic metastases from colorectal cancer: Resection or not

Abstract: This review evaluates the available evidence dealing with the natural history of hepatic metastases in patients with colorectal cancer. Methods of detection of such metastases are discussed and the factors influencing survival after surgical resection are reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0
1

Year Published

1990
1990
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(27 citation statements)
references
References 30 publications
2
24
0
1
Order By: Relevance
“…The indications for liver resection for colorectal metastases are still controversial [ 1, 2,11,12]. Authors who started to perform liver resection in the early 1950s only report on very well selected cases with more than threefourths of their patients having symptomatic, but solitary lesions.…”
Section: Discussionmentioning
confidence: 99%
“…The indications for liver resection for colorectal metastases are still controversial [ 1, 2,11,12]. Authors who started to perform liver resection in the early 1950s only report on very well selected cases with more than threefourths of their patients having symptomatic, but solitary lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Five-year survival rates of up to 35% have been reported for patients amenable for partial hepatic resection (Hughes, 1986;Scheele, 1990;Van Ooyen, 1992;Sugihara, 1993;Que, 1994). Unfortunately, the vast majority of colorectal metastases confined to the liver are considered to be unresectable (Greenway, 1988;Cady, 1991;Genari, 1992). In addition, systemic chemotherapy has so far failed to provide satisfactory results in these cases (Kemeny, 1983(Kemeny, , 1987.…”
mentioning
confidence: 99%
“…Although such favorable results from surgical treatment have provided the rationale for resection of liver metastases, at least 75% of patients still develop recurrence within 5 years of the initial hepatectomy [4]. Indeed, some investigators have reported that repeated hepatectomy for recurrent liver metastases may be efficacious [5]. …”
Section: Introductionmentioning
confidence: 99%